Effects of the Novel IDO Inhibitor DWG-1036 on the Behavior of Male and Female 3xTg-AD Mice - Fertan, Emre; Stover, Kurt R.J.; Brant, Michael G.; Stafford, Paul M.; Kelly, Brendan; Diez-Cecilia, Elena; Wong, Aimée A.; Weaver, Donald F.; Brown, Richard E. (Frontiers in Pharmacology, 2019)
The kynurenine pathway metabolizes tryptophan into nicotinamide adenine dinucleotide, producing a number of intermediary metabolites, including 3-hydroxy kynurenine and quinolinic acid, which are involved in the neurodegenerative mechanisms that underlie Alzheimer’s disease (AD). Indolamine 2,3-dioxygenase (IDO), the first and rate-limiting enzyme of this pathway, is increased in AD and it has been hypothesized that blocking this enzyme may slow the progression of AD. In this study, we treated male and female 3xTg-AD and wild type mice with the novel IDO inhibitor DWG-1036 (80mg/kg) or vehicle (distilled water) from 2 to 6 months of age and then tested them in a battery of behavioural tests that measured spatial learning and memory (Barnes maze), working memory (trace fear conditioning), motor coordination and learning (rotarod), anxiety (elevated plus maze), and depression (tail suspension test). The 3xTg-AD mice treated with DWG-1036 showed better memory in the trace fear conditioning task and significant improvements in learning but poorer spatial memory in the Barnes maze. DWG-1036 treatment also ameliorated the behaviours associated with increased anxiety in the elevated plus maze and depression-like behaviours in the tail suspension test in 3xTg-AD mice. However, the effects of DWG-1036 treatment on the behavioural tasks were variable and sex differences were apparent. In addition, high doses of DWG-1036 resulted in reduced body weight, particularly in females. Taken together, our results suggest that the kynurenine pathway is a promising target for treating AD, but more work is needed to determine the effective compounds, examine sex differences, and understand the side effects of the compounds.